Gestión administrativa y su incidencia en el sistema de control presupuestario de la dirección distrital 13d08 pichincha – educación, año 2014. Guía de control presupuestario. - Mendoza Intriago, Johanna Elizabeth (2025)
This research was conducted in the District Direction 13D08 Pichincha - Education, whose main activity strengthen and direct educational services to the educational community, serving local and cultural realities of the canton Pichincha. Its objective is focused on assessing the impact of the administration in the budget control system of the District Direction 13D08 Pichincha - Education, based on the question: What is the impact of administrative management in the system of budgetary control of the District Direction 13D08 Pichincha - Education? It is important to state that there is little knowledge of the administrative handling by staff, which makes the operating and administrative budget lines and controlling financial activities; and thus the proper implementation of integrated public finance system. The hypothesis corresponds to an inadequate administration that adversely affects the system of budgetary control 13D08 Pichincha District Direction - Education, in order to demonstrate the above variables in the problem of study. Education - Based on the described problems developing a guide to budget control will correct the deficiencies, contributing to the achievement of corporate goals and quality of public spending Pichincha District Directorate intends 13D08. In addition, this thesis seeks to raise awareness among managers of public institutions on the importance of representing the staff selected with skills and expertise in administrative management for the proper development of activities, being the axis of the point in the organizations success.